Implementation of Patil Lele Traditional Game As Ethnomathematics to Improve Student’s Perspective to Mathematics - Nuzul Putri Rahmawati; Akhsanul In’am; Mayang Dintarini (Department of Mathematics Education University of Muhammadiyah Malang, 2019)
The aim of this research is as an effort students’ perspective on mathematics and the preservation of traditional Indonesian games. As for the background of this writing, because Indonesia is a country that has a diversity of cultures, one of them is traditional games. The current of globalization in Indonesia has the effect of threatening extinction towards various traditional Indonesian games. On other hand, the problem is the majority of students consider mathematics learning is difficult and unpleasant lesson. This research takes one of the traditional Indonesian games namely patil lele to be implicated in mathematics learning. This research used descriptive qualitative research with the aim of describing, explaining, and interpreting the implementation of traditional game patil lele as ethnomatematics qualitatively using observation, documentation, and filling questionnaires and tests. The results showed that the use of patil lele games introduce students to traditional games, foster social attitudes, collaborate with students, and help students understand the concept of distance between points. After applying traditional patil lele games, students can get to know the game. By introducing this game, students can love their own culture that is Indonesian culture with their participation in preserving traditional patil lele games. The application of traditional patil lele games can reduce the abstractness of mathematics by visualizing the material of distance between points through the game. Thus, the implementation can provide a good image of mathematics subjects students’ perspective